(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Pregnancy is a potentially glucose intolerant condition. Insulin sensitivity decreases as the pregnancy advances. At the later stage of pregnancy, some women develop Gestational Diabetes Mellitus (GDM) particularly obese with pre-existing insulin resistance. Insulin is recognized as the gold standard for the treatment of GDM. However, difficulty in administration with multiple daily injections, potential for hypoglycemia, and increase in appetite and weight, make this therapeutic option troublesome for many pregnant patients. Oral hypoglycaemic drugs have been viewed with suspicion for many years in the management of women with diabetes during pregnancy or breastfeeding. However, recent data from well designed trials and meta-analysis may contribute a visible change in practice in terms of oral agents, especially metformin in gestational diabetes. Some cohort data are available and randomized trials are currently in progress to compare metformin with insulin. Evidence is emerging that metformin may improve insulin sensitivity during pregnancy. This may be beneficial in GDM. Use of metformin in pregnancy has opened a new horizon for GDM management. The aim of this article is to review the safety, efficacy and future of metformin in diabetic pregnancy, thus contributing meaningfully in safe motherhood. Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 70-77